The local limit theorem for recurrent Events - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене, Локальная предельная теорема для рекуррентных событий A. Aleškevičienė, Lokalinė ribinė teorema rekurentiniams įvykiams